Role of lncRNAs in acute pancreatitis: pathogenesis, diagnosis, and therapy - Deng, Jie; Song, Ziying; Li, Xiaolan; Shi, Huiqing; Huang, Shangqing; Tang, Lijun (Frontiers in Genetics, 2023)
Acute pancreatitis (AP) is one of the most common acute abdominal diseases characterized by an injury and inflammatory disorder of the pancreas with complicated pathological mechanisms. Long non-coding RNAs (lncRNAs) have been shown to play an important role in various physiological and pathological processes in humans, and they have emerged as potential biomarkers of diagnosis and therapeutic targets in various diseases. Recently, accumulating evidence has shown significant alterations in the expression of lncRNAs, which are involved in the pathogenesis of AP, such as premature trypsinogen activation, impaired autophagy, inflammatory response, and acinar cell death. Moreover, lncRNAs can be the direct target of AP treatment and show potential as biomarkers for the diagnosis. Thus, in this review, we focus on the role of lncRNAs in the pathogenesis, diagnosis, and therapy of AP and emphasize the future directions to study lncRNAs in AP, providing new insight into understanding the cellular and molecular mechanisms of AP and seeking novel biomarkers for the diagnosis and therapeutic targets to improve clinical management in the future.